Multifunctional PdH-hydride MOFs for synergistic hydrogen and photothermal antibacterial therapy in accelerated wound healing - Wang, Qing; Zhang, Daixing; Qi, Yining; Huang, Changbao; Ding, Dejun; Liu, Chuanliang (Frontiers in Pharmacology, 2025)
IntroductionThe growing threat of bacterial infections poses a critical challenge to public health, underscoring the urgent need for innovative antibacterial agents and therapeutic strategies. In response, we have developed a multifunctional nanoplatform based on palladium-hydride metal–organic frameworks (P(H)ZPAg) for synergistic hydrogen and photothermal antibacterial therapy.MethodsThis nanoplatform integrates palladium hydride (PdH) encapsulated within a zeolitic imidazolate framework (ZIF-8), surface modification with polydopamine (PDA), and in situ generation of silver nanoparticles (Ag NPs) to achieve enhanced antibacterial efficacy. Comprehensive characterization was performed to assess hydrogen release kinetics, photothermal performance, and silver-mediated bactericidal activity. The therapeutic potential of P(H)ZPAg was further evaluated in vivo using a Staphylococcus aureus-infected rat wound model.ResultsThe P(H)ZPAg nanoplatform demonstrated a successful combination of hydrogen release, photothermal conversion, and silver ion-based antibacterial mechanisms. In vitro assays revealed potent synergistic antibacterial effects against both Escherichia coli and Staphylococcus aureus. In vivo studies showed that treatment with P(H)ZPAg nanoparticles significantly enhanced wound healing and bacterial clearance compared to control groups.DiscussionThese findings highlight the potential of combining hydrogen therapy, photothermal therapy, and silver ion release within a single nanoplatform to markedly improve antibacterial outcomes. This study presents a promising strategy for the development of multifunctional nanotherapeutics, offering a novel and effective approach for managing topical bacterial infections and promoting wound healing.